2018
DOI: 10.1007/s10695-018-0526-9
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and antioxidant responses in juvenile Brazilian flounder Paralichthys orbignyanus exposed to sublethal levels of nitrite

Abstract: This study evaluated the effects of short-term exposure to sublethal levels of nitrite on oxidative stress parameters and histology of juvenile Brazilian flounder Paralichthys orbignyanus. An assessment of fish recovery was also performed. Fish were exposed to 0.08 (control), 5.72, 10.43, and 15.27 NO-N mg L for 10 days followed by the same recovery time. Gill, liver, and muscle samples were collected after 1, 5, and 10 days of exposure and after recovery for the measurement of antioxidant capacity against per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 51 publications
1
21
0
Order By: Relevance
“…Interestingly, in circumneutral pH, an elevation of water hardness reduced GST activity in the gills on these same days (1 and 5), which suggests that, in this tissue, HWH had no positive effect when pacus were exposed to circumneutral pH. The ACAP assessment sheds light on the overall antioxidant status of the fish against peroxyl radicals (Maltez et al, 2018), which was compromised in the kidney of pacus through alkaline pH exposure on day 5. In addition, a possible explanation for lower gills ACAP (higher relative area) in alkaline pH with HWH on day 1 was due to a compensatory effect, because an increase in GST activity and a reduction in TBARS levels were observed under these conditions.…”
Section: E190032[7]mentioning
confidence: 89%
See 2 more Smart Citations
“…Interestingly, in circumneutral pH, an elevation of water hardness reduced GST activity in the gills on these same days (1 and 5), which suggests that, in this tissue, HWH had no positive effect when pacus were exposed to circumneutral pH. The ACAP assessment sheds light on the overall antioxidant status of the fish against peroxyl radicals (Maltez et al, 2018), which was compromised in the kidney of pacus through alkaline pH exposure on day 5. In addition, a possible explanation for lower gills ACAP (higher relative area) in alkaline pH with HWH on day 1 was due to a compensatory effect, because an increase in GST activity and a reduction in TBARS levels were observed under these conditions.…”
Section: E190032[7]mentioning
confidence: 89%
“…The lipid peroxidation levels were measured according to Oakes, Van Der Kraak (2003) by thiobarbituric acid reactive substances (TBARS) content. The TBARS content was determined by the quantification of MDA (malondialdehyde) following the protocol described in detail by Maltez et al (2018). The data are expressed as nmol TMP (tetramethoxypropane (ACROS Organics)) mg wet tissue −1 .…”
Section: Sample Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulation of NO 2 − in tissues can result in mass mortality of fish as several functions such as gas transport, ion regulation, and cardiovascular, endocrine and excretory processes are affected (Jensen, ; Svobodová et al, ). In addition, exposure to nitrite can also induce oxidative stress and antioxidant responses in juvenile Brazilian flounder (Maltez et al, ). Nitrite has affinity for the branchial chloride uptake mechanism, that is, NO 2 − can replace Cl − in the chloride/bicarbonate (Cl − /HCO 3 − ) gill transporters (Jensen, ).…”
Section: Introductionmentioning
confidence: 99%
“…A condition of oxidative stress can be triggered by high production of ROS or due to the compromise of the antioxidant defence system, or by the combination of both situations (Halliwell & Gutteridge, 2015). Recent studies showed that fish exposure to nitrite can compromise the antioxidant system (Maltez et al, 2018) and also induced increased ROS (Sun et al, 2014) and RNS as nitric oxide (NO) production, which also have capacity to cause oxidative damage (Jensen et al, 2015; Jensen & Hansen, 2011).…”
Section: Discussionmentioning
confidence: 99%